ANALISIS KINERJA PEGAWAI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KOTA SEMARANG - Putra, Rabindra Rahadiyan; Nurcahyanto, Herbasuki; Suryaningsih, Margaretha (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This study aimed to describe the performance of staff at the Department of Transportation, Communication and Information Semarang and to determine what aspects cause the performance of staff at the Department of Transportation, Communication and Information Semarang not optimal. Loci used in this study is in the Department of Transportation, Communication and Information Semarang. This study used a qualitative research method is descriptive. The subjects in this study consisted of four (4) key informantBased on the results of the study show that the performance of staff at the Department of Transportation, Communication and Information Semarang can be categorized Well although there are some dimensions are still unwell. Aspects that affect the performance of employees keoptimalan Department of Transportation, Communication and Information Semarang which aspects of competence and motivational aspects.The conclusion of this study is the overall performance of employees of the Department of Transportation, Communication and Information Semarang has been good, and aspects of competence and motivation keoptimalan indeed affect the performance of the Department of Transportation, Communication and Information Semarang. Based on these conclusions, the researchers recommend to the Department of Transportation, Communication and Information Semarang to correct dimensions is still considered less well so that optimal performance can be achieved more.